An economic analysis of public law Demos and Agora - Dellis, Georges (Edward Elgar Publishing Limited, 2021)
This original and insightful book considers the ways in which public law, which emphasises legality (the Demos), and economics, a science oriented towards the markets (the Agora), intertwine. Throughout, George Dellis argues that the concepts of legality and efficiency should not be perceived separately."